2009
DOI: 10.1111/j.1468-2494.2009.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of 3D human skin EpiDermTM model: effects of skin moisturizers

Abstract: The objective of this study was to determine the effects of skin moisturizers on total antioxidant capacity (TAC) of human skin using EpiDerm model. Three different skin moisturizers containing antioxidant ingredients (samples 1-3) or aloe vera extract were topically applied to EpiDerm units and incubated for 2 and 24 h to determine acute and longer-term effects of applied samples on TAC and glutathione peroxidase activity in medium and/or homogenized skin tissues. Total antioxidant capacity in medium and skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…The skin consists of an interface between the human body and the environment. Therefore, it is exposed to endogenous and exogenous oxidant agents that could generate many free radicals [1]. Oxidative stress arises when the formation of free radicals is greater than its elimination by the antioxidant defense system of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The skin consists of an interface between the human body and the environment. Therefore, it is exposed to endogenous and exogenous oxidant agents that could generate many free radicals [1]. Oxidative stress arises when the formation of free radicals is greater than its elimination by the antioxidant defense system of the body.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the stability of antioxidants in the tapes was explored in different conditions for several time frames. A close review of the literature revealed the usage of a variety of storage conditions in skin antioxidant studies, such as −70 °C in a study by Grazul-Bilska et al [ 54 ], 4 °C for biopsy samples in other studies [ 31 , 55 ] and −20 °C for the separated epidermis, biopsies and excised skin in work by others [ 56 , 57 , 58 ]. Furthermore, a temperature of −20 °C was found to be effective in the storage of tapes after tape stripping for penetration studies [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example Grazul‐Bilska et al. determined the effects of skin moisturizers on total antioxidant capacity of human skin using EpiDerm™ (MatTek Corporation, Ashland, MA, USA) model and glutathione peroxidase activity as a marker of antioxidant capacity.…”
Section: In Vitro Antioxidant Activity In Skin Cultured Cellsmentioning
confidence: 99%